2015
DOI: 10.1016/j.physletb.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Isoscalar and isovector pairing in a formalism of quartets

Abstract: Isoscalar (T=0,J=1) and isovector (T=1,J=0) pairing correlations in the ground state of self-conjugate nuclei are treated in terms of alpha-like quartets built by two protons and two neutrons coupled to total isospin T=0 and total angular momentum J=0. Quartets are constructed dynamically via an iterative variational procedure and the ground state is represented as a product of such quartets. It is shown that the quartet formalism describes accurately the ground state energies of realistic isovector plus isosc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…In Table II the QCM results are compared to the exact results and to the results of the QM approximation (18) presented in Ref. [17]. One can see that the QCM approximation, in which it is supposed that all quartets have the same structure, gives accurate results, comparable with the QM approximation.…”
Section: Omentioning
confidence: 67%
See 4 more Smart Citations
“…In Table II the QCM results are compared to the exact results and to the results of the QM approximation (18) presented in Ref. [17]. One can see that the QCM approximation, in which it is supposed that all quartets have the same structure, gives accurate results, comparable with the QM approximation.…”
Section: Omentioning
confidence: 67%
“…We have also shown that in the QCM approximation the correlations in the two pairing channels coexist for any admixture of isovector and isoscalar pairing forces, which confirms the findings of Refs. [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations